SLEEP DISORDERS AND HYPERTENSION: PATHOPHYSIOLOGICAL MECHANISMS, EPIDEMIOLOGICAL EVIDENCE AND CLINICAL IMPLICATIONS - Ewa Dapkiewicz; Dawid Gąsowski; Sylwia Haba; Katarzyna Łysynkiewicz; Zuzanna Wątek; Patrycja Krawczyk; Izabela Grzyb; Jan Szewczyk; Alicja Smolińska; Maria Bołoz (Archiv Euromedica, 2026)
Background Hypertension remains a major global health challenge and an important risk factor for cardiovascular disease. Increasing evidence indicates that sleep disorders and adverse sleep patterns are associated with blood pressure dysregulation and may contribute to the development or persistence of hypertension. Aim This narrative review aimed to evaluate the pathophysiological mechanisms, epidemiological evidence, and clinical implications of the relationship between sleep disorders and hypertension, with particular attention to poorly controlled and resistant hypertension. Materials and Methods A narrative literature review was conducted using PubMed/MEDLINE and Google Scholar from database inception to March 2026. Human observational and interventional studies, systematic reviews, meta-analyses, narrative reviews, and relevant clinical guidelines or position statements were included. A total of 149 publications were included in the narrative synthesis. Results Sleep disorders and adverse sleep patterns are associated with blood pressure dysregulation through sympathetic nervous system activation, impaired nocturnal blood pressure dipping, activation of the hypothalamic-pituitary-adrenal and renin-angiotensin-aldosterone systems, endothelial dysfunction, inflammation, oxidative stress, and, in obstructive sleep apnea, recurrent intermittent hypoxia. The strongest and most consistent evidence concerns obstructive sleep apnea, particularly in patients with resistant or poorly controlled hypertension. Short sleep duration, insomnia accompanied by objectively reduced sleep, and circadian disruption are also associated with hypertension, although the evidence is less consistent. Findings regarding restless legs syndrome and periodic limb movements during sleep remain heterogeneous. Conclusions Sleep disorders and adverse sleep patterns may contribute to impaired blood pressure regulation. Obstructive sleep apnea has the strongest documented association with hypertension, especially in patients with resistant or poorly controlled hypertension. Evidence for short sleep duration, insomnia with objectively reduced sleep, and circadian disruption is less consistent, while findings for restless legs syndrome and periodic limb movements during sleep remain heterogeneous. Assessment of sleep disorders and sleep patterns may help identify potentially modifiable factors contributing to inadequate blood pressure control.